Dlk1-Mediated Temporal Regulation of Notch Signaling Is Required for Differentiation of Alveolar Type II to Type I Cells during Repair - Johanna Finn; Kilian Sottoriva; Kostandin V. Pajcini; Jan K. Kitajewski; Chang Chen; Wei Zhang; Asrar B. Malik; Yuru Liu (Cell Reports, 2019)
Summary: Lung alveolar type I cells (AT1) and alveolar type II cells (AT2) regulate the structural integrity and function of alveoli. AT1, covering ∼95% of the surface area, are responsible for gas exchange, whereas AT2 serve multiple functions, including alveolar repair through proliferation and differentiation into AT1. However, the signaling mechanisms for alveolar repair remain unclear. Here, we demonstrate, in Pseudomonas aeruginosa-induced acute lung injury in mice, that non-canonical Notch ligand Dlk1 (delta-like 1 homolog) is essential for AT2-to-AT1 differentiation. Notch signaling was activated in AT2 at the onset of repair but later suppressed by Dlk1. Deletion of Dlk1 in AT2 induced persistent Notch activation, resulting in stalled transition to AT1 and accumulation of an intermediate cell population that expressed low levels of both AT1 and AT2 markers. Thus, Dlk1 expression leads to precisely timed inhibition of Notch signaling and activates AT2-to-AT1 differentiation, leading to alveolar repair. : Finn et al. show that Notch signaling is activated in type II cells after alveolar injury but that subsequent Dlk1-mediated inhibition of Notch is required for complete type II-to-type I cell transition and alveolar repair. Thus, Dlk1 and Notch are potential therapeutic targets for treatment of lung injury. Keywords: lung, alveoli, progenitor type II cell, Notch, Dlk1